1986
DOI: 10.2307/2388757
|View full text |Cite
|
Sign up to set email alerts
|

Ecology, Distribution, Harvest, and Conservation of the Amazonian Manatee Trichechus inunguis in Ecuador

Abstract: Recent summaries of the distribution of the Amazonian manatee Trichechus inunguis record specimens from much of the Central Amazon Basin in Brazil, eastern Peru, and extreme southeastern Colombia, but not Ecuador. During October and November of 1983 we searched for manatees in the Rio Aguarico and Rio Cuyabeno systems of Napo Province, eastern Ecuador. Herein we document the existence of Amazonian manatees in Ecuador, provide rough estimates of their current distribution, describe several aspects of their ecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 12 publications
1
26
0
3
Order By: Relevance
“…The hyacinth Eichornia crassipes was the third most frequent plant in t he digestive tracts and faeces analyzed, constituting 11.2% of the Amazonian manatees diet. Marmol (1976) in Peru and Timm et al (1986) in Ecuador, also found Amazonian manatee feeding on this species. Some have noted that the West Indian manatees only ate the emergent part of hyacinth, ignoring the roots (Lomolino, 1977).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The hyacinth Eichornia crassipes was the third most frequent plant in t he digestive tracts and faeces analyzed, constituting 11.2% of the Amazonian manatees diet. Marmol (1976) in Peru and Timm et al (1986) in Ecuador, also found Amazonian manatee feeding on this species. Some have noted that the West Indian manatees only ate the emergent part of hyacinth, ignoring the roots (Lomolino, 1977).…”
Section: Resultsmentioning
confidence: 90%
“…It ranges from Marajó Island (Brazil) to the sources of the Amazon basin rivers in Columbia, Peru and Ecuador (Timm et al, 1986). It is present in all the major draining system tributaries of the Amazon river, where its distribution is apparently restricted to two locations: calm waters and lakes with aquatic vegetation (Best, 1984;Rosas et al,1991;Rosas, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sirenia order is the only order of aquatic mammal's survivors that are exclusively herbivorous [4]. This animal is an endemic species of the Amazon basin, occupying water bodies in Brazil, Colombia, Ecuador and Peru [1,3,[5][6][7], being reported in the latter mainly in rivers within Loreto region [2,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The Amazonian manatee is a non-ruminant herbivore that feeds on a wide variety of aquatic and semiaquatic plants (Guterres et al, 2008). The species plays an important role in the ecosystem, returning more than half of the ingested material to the environment as feces and urine, and is therefore essential to primary production (Best, 1984;Timm et al, 1986). The commercial exploitation (Domning, 1982), along with the slow rate of reproduction (Rodrigues et al, 2008), have seriously reduced the Amazonian manatee population (IUCN, 2008).…”
Section: Introductionmentioning
confidence: 99%